Study of the Responsibility of Independent Appraisal Services of Bank Collateral Related to the Auction Value of Execution of Collateral Objects - Atikawati Wiseno Putri, Febri (Ann Publisher, 2023)
In providing bank credit, collateral must be submitted for credit return. Collateral certificates/fixed assets are most favored by creditors/banks. The provision of credit by banks cannot be separated from the assessment of collateral first. The Internal Bank carries out the assessment, which can be done by the Public Appraiser or KJPP (Public Appraisal Service Office). The Public Appraiser will provide a report on the value of collateral submitted by the debtor to be used as a basis by the bank to determine the Ceiling (maximum amount of credit). The position of creditors who are more dominant in the process of granting credit will more or less affect the market value and liquidation of collateral. In this case, the debtor has a risk to the value of the collateral that the Public Appraiser has determined if the collateral goes bankrupt. This research uses a legislative and conceptual approach.